(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Educating women in India has been a priority for the government and civil society alikebecause of the vital role that educated women can play in the progress of the nation. The ability to adaptto adversity, to question one’s conventional position, and to make positive life changes are all madepossible by education, making it a crucial step towards women’s empowerment. India is on track tobecome a powerhouse and a developed nation by the year 2020, thus we must not overlook thesignificance of education in advancing women’s equality in this country. Slow progress is being made toincrease rural women’s access to higher education. This indicates that many women in our nation arestill uneducated and hence vulnerable to being taken advantage of.Women’s education is one of themost effective means of social transformation. Getting an education helps level the playing field andraises their social standing at home.